Infectious Disease and Maternal Factors Associated with Stunting among Children in Mimika, Central Papua: A Case–Control Study - Rosmin Mariati Tingginehe; Muhamad Sahiddin (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Child stunting persists as a critical nutritional challenge in Indonesia, with a disproportionately high burden in its eastern provinces, where infectious diseases are endemic. This study aimed to identify the determinants of stunting among children aged 24–59 months in Mimika District, Papua Tengah. A retrospective case–control study was carried out in the service area of the Pasar Sentral Primary Health Center. The analysis included 330 children aged 24–59 months, including 110 stunted cases and 220 controls, who were recruited from the same community health posts; controls were selected using simple random sampling with a 1:2 case-to-control ratio Information was obtained through structured interviews with caregivers and the verification of health records, including maternal and child health books and the electronic community-based nutrition recording system (e-PPGM). The associations between potential risk factors and stunting were evaluated using chi-square tests, followed by multivariable logistic regression analysis. A history of infectious disease had the strongest association (aOR 4.81; 95% CI 2.69–8.58). Additional factors associated with stunting were household income below the provincial minimum wage (aOR 3.52; 95% CI 1.98–6.26), low maternal education (aOR 2.92; 95% CI 1.63–5.23), low birth weight (aOR 2.78; 95% CI 1.37–5.64), incomplete immunization (aOR 2.21; 95% CI 1.24–3.94), lack of exclusive breastfeeding (aOR 2.32; 95% CI 1.29–4.16), incomplete antenatal care visits (aOR 1.96; 95% CI 1.10–3.49), and maternal anemia during pregnancy (aOR 1.85; 95% CI 1.04–3.30). Integrated strategies focusing on infection prevention, maternal and child health services, and household living conditions are needed to reduce stunting in malaria-endemic areas.